Changes in corticospinal drive to spinal motoneurones following tablet‐based practice of manual dexterity. Issue 2 (26th January 2016) - Larsen, Lisbeth H.; Jensen, Thor; Christensen, Mark S.; Lundbye‐Jensen, Jesper; Langberg, Henning; Nielsen, Jens B.
Abstract: The use of touch screens, which require a high level of manual dexterity, has exploded since the development of smartphone and tablet technology. Manual dexterity relies on effective corticospinal control of finger muscles, and we therefore hypothesized that corticospinal drive to finger muscles can be optimized by tablet‐based motor practice. To investigate this, sixteen able‐bodied females practiced a tablet‐based game (3 × 10 min) with their nondominant hand requiring incrementally fast and precise pinching movements involving the thumb and index fingers. The study was designed as a semirandomized crossover study where the participants attended one practice‐ and one control session. Before and after each session electrophysiological recordings were obtained during three blocks of 50 precision pinch movements in a standardized setup resembling the practiced task. Data recorded during movements included electroencephalographic (EEG) activity from primary motor cortex and electromyographic (EMG) activity from first dorsal interosseous (FDI) and abductor pollicis brevis (APB) muscles. Changes in the corticospinal drive were evaluated from coupling in the frequency domain (coherence) between EEG–EMG and EMG–EMG activity. Following motor practice performance improved significantly and a significant increase in EEG‐EMGAPB and EMGAPB ‐EMGFDI coherence in the beta band (15–30 Hz) was observed. No changes were observed after the control session. Our results show that tablet‐based motor practice is associated with changes in the common corticospinal drive to spinal motoneurons involved in manual dexterity. Tablet‐based motor practice may be a motivating training tool for stroke patients who struggle with loss of dexterity. Abstract : Operation of touch screen devices requires manual dexterity that relies on effective corticospinal control of the finger muscles. Here we demonstrate that 30 minutes of tablet‐based motor practice with a specialized application improves performance and is accompanied by changes in the central nervous system, that is, in the coupling between the motor cortex and the spinal level that is the α ‐motoneuronal activity.